To Study the Outcome of Low-Cost Negative-Pressure Wound Therapy Using Wall-Mounted Vacuum Device in the Treatment of Open Wounds - Neeraj Jain; Ravi Kant Jain; Ajay Sabhnani (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: The Primary objective of this prospective study is to study the rate of infection, number of days required for formation of healthy granulation tissue, healing of soft tissue injury and number of days of hospital stay and cost effectiveness associated with soft tissue injury treated by Vacuum Assisted closure therapy. Methods: This is a prospective observational study of 30 patients presenting with open musculoskeletal injuries in extremities that required coverage procedures in the department of Orthopaedics, Sri Aurobindo Medical College and PG Institute, Indore. All these patients had undergone wound debridement and fracture fixation. This was followed by application of Vacuum Assisted Closure (VAC). The infection rate analysed by clinical findings and investigations. Assessment of these wound(s) were done on a regular basis by wound bed score. Assessment of rate of granulation was done on every 3rd day. Based on the rate of granulation, definitive surgical intervention (skin grafting, secondary closures and flap cover procedures) was done. The patient was sent home after performing the definitive surgical intervention. Results: The infection rate was low when compared to literature study of conventional dressings. The primary wound coverage can be done earlier wound healing was also faster in patients. Conclusion: This is a simple and low cost method for treating soft tissue injury associated with severe open fractures. It can be done even in peripheral hospitals with low resources. The rate of granulation tissue formation is good with vacuum assisted closure. Also compliance of patient is good in vacuum assisted closure therapy.VAC dressing also provided the wound ready for SSG or flap rotation early as assessed by wound bed score.